Learning attitudes in excellent and average university students - Bernardo GARGALLO LÓPEZ; Gonzalo ALMERICH CERVERÓ; Eloína GARCÍA FÉLIX; Miguel Ángel JIMÉNEZ RODRÍGUEZ (Education in the Knowledge Society, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->We seek to analyse how the best students on entry to University work in order to transfer it to the rest of the University community. We used the AUSLQ questionnaire (Attitudes of University Students toward Learning Questionnaire) to assess the attitudes of a sample of 148 excellent students selected from 11 degrees from 9 centers of the Polytechnic University of Valencia, and we compared the results with those of a sample of 133 average students of the same centers. We found that excellent students developed better attitudes than average students. We also found that learning attitudes had an influence on the academic achievement. The available data allow us to affirm that the professors can enhance the deep approach by using adequate teaching and assessment methodologies.